Camp Can't - Gallagher, Diana G. (Gallagher, Diana G. Claudia Cristina Cortez., 2008)
Thirteen-year-old Claudia wants to prove that she should be a junior counselor at Blue River Camp next year, but first she must face mean girls, the boy she has a crush on, a seven-year-old rascal she often babysits, her own bad luck, and a challenging swimming test.